2013
DOI: 10.5489/cuaj.1562
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in urology training: A national survey of senior residents

Abstract: Introduction: We explore the attitudes and experience of urology residents toward acute and chronic pain management during their training. Method: A convenience sample of Canadian Urology chief residents were invited to complete an anonymous questionnaire involving both open and closed-ended questions using a 5-point Likert scale. Descriptive and quantitative statistics were used to analyze the attitudes toward pain management, including their experience and training issues. Results: The response rate was 97%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Urologists, in particular, manage chronic non-cancer pains such as chronic prostatitis/chronic pelvic syndrome, interstitial cystitis, chronic epididymitis, and orchiodynia, in addition to chronic cancer-related pain, acute renal colic pain, and pain occurring in an acute surgical setting. [21][22][23][24] Similar to other surgical specialties, most opioid prescriptions written in academic centres are written by urologists in training, highlighting the importance of an in-depth understanding of pain management options. [23][24][25][26] However, studies involving medical oncologists and surgeons demonstrated clear knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urologists, in particular, manage chronic non-cancer pains such as chronic prostatitis/chronic pelvic syndrome, interstitial cystitis, chronic epididymitis, and orchiodynia, in addition to chronic cancer-related pain, acute renal colic pain, and pain occurring in an acute surgical setting. [21][22][23][24] Similar to other surgical specialties, most opioid prescriptions written in academic centres are written by urologists in training, highlighting the importance of an in-depth understanding of pain management options. [23][24][25][26] However, studies involving medical oncologists and surgeons demonstrated clear knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Similar to other surgical specialties, most opioid prescriptions written in academic centres are written by urologists in training, highlighting the importance of an in-depth understanding of pain management options. [23][24][25][26] However, studies involving medical oncologists and surgeons demonstrated clear knowledge gaps. 24,27,28 A recent survey of US surgical program directors found that only 20% of training programs have mandatory opioid prescribing education as part of their curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey by Pace et al in 2013, chief residents in Canadian training programs had reported very little comfort in managing chronic non-cancer pain, with minimal knowledge of opioid prescribing guidelines. 5 The majority reported that they got most of their knowledge around use of opioid prescribing from their senior residents. These issues need to be addressed by our community and the efforts by the CMPA and our provincial colleges should help.…”
mentioning
confidence: 99%
“…4 Less than a quarter of the respondents received formal training during their residency program. Managing pain turns out to be just another "thing to do" and not a main focus of patient care.…”
mentioning
confidence: 99%